Preoperative FeNO as a screening indicator of pulmonary complications after abdominal surgery in patients over 60 years old. (21st May 2015) - Pi, Xin; Wang, Changsong; Li, Yue; Zheng, Juanjuan; Cui, Yinghua; Guo, Lei; Lin, Ziwei; Zhang, Xin; Li, Enyou
Abstract: The incidence of pulmonary complications after abdominal surgery is higher than that of cardiac complications. The perioperative factors currently used to assess the risk of postoperative pulmonary complications (PPCs) are imperfect. FeNO is a marker of respiratory system disease related to the airway inflammatory response and bronchial hyperresponsiveness; it may be a new indicator to screen PPCs. A total of 162 patients over 60 years old scheduled for major abdominal surgery under general anesthesia were chosen to measure their preoperative FeNO level. Statistical analyses including the receiver operating characteristic (ROC) and general linear regression were used to analyze the relationships of FeNO with PPCs and other parameters. The medians and quartiles of preoperative FeNO were 14.33 (9.67–21.10) ppb; the geometric mean was 14.25 ppb. Preoperative FeNO correlated to age ( P < 0.05 ), and the coefficient of association was 0.267. ROC curve analysis of FeNO and PPCs resulted in a high probability with an area under the curve of 0.747 ( p = 0.001, 95% confidence interval =0.602–0.893). The cut-off level was 30.2 ppb, with 47.06% sensitivity and 93.10% specificity. The positive predictive value of the cut-off was 42.11% and negative predictive value was 93.70%. OR value was 10.83. The magnitude of FeNO in the PPCs group was larger than that in the non-PPCs groups 26.20 (11.55 – 39.20) versus 13.50 (9.55–20.00); p = 0.008). Preoperative FeNO levels may be used to screen the patients over 60 years old undergoing abdominal surgery with a lower probability to suffer PPCs whoes FeNO values less than 30.2 ppb.